2021
DOI: 10.1021/acs.inorgchem.1c00987
|View full text |Cite
|
Sign up to set email alerts
|

Linear and Bent Nitric Oxide Ligand Binding in an Asymmetric Butterfly Complex: CoMoCo′

Abstract: Two synthetic approaches to install metallodithiolate ligands on molybdenum centers using the synthons [Mo 2 (CH 3 CN) 10 ] 4+ and (N 2 S 2 )Co(NO) [N 2 S 2 = N,N-bis(2-mercaptoethyl)-1,4-diazacycloheptane and NO = nitric oxide], or [Mo(NO) 2 (CH 3 CN) 4 ] 2+ (CH 3 CN = acetonitrile) and [(N 2 S 2 )Co] 2 lead to a bisnitrosylated, trimetallic dication, CoMoCo′. This unique asymmetric butterfly complex, with S = 1, has a bent NO within the small {Co(NO)} 8 wing (denoted as Co), reflecting Co III (NO − ), and is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Previously, we determined CoMoCo′ , Figure , to have a triplet ground state originating from intermediate spin Co III on the Co′ . To gain insight into this triplet state, we investigated the magnetic moment temperature dependence, Figure c.…”
Section: Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, we determined CoMoCo′ , Figure , to have a triplet ground state originating from intermediate spin Co III on the Co′ . To gain insight into this triplet state, we investigated the magnetic moment temperature dependence, Figure c.…”
Section: Results and Discussionmentioning
confidence: 99%
“…An application of these strategies toward derivatives of molybdenum, expected to be analogous to a class of [(bis-diphosphine) 2 M(NO)X] n+ molecules, 19 led to an unusual, asymmetric version of the basket structure of Figure 2. 20 Synthons include the [Mo 2 (MeCN) 10 ] 4+ source, which in our first studies in this area found that combination with (N 2 S 2 )Ni produced the Mo 2 Ni 4 paddlewheel structure (Figure 1d). 21 However, for (N 2 S 2 )Co(NO), as displayed in Figure 2, two cobalt ligands assemble about a single Mo atom.…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations